Aldosterone synthase (CYP11B2) deficiency among Palestinian infants: Three novel variants and genetic heterogeneity. Issue 4 (13th January 2021) - Faingelernt, Yaniv; Hershkovitz, Eli; Abu‐Libdeh, Bassam; Abedrabbo, Amal; Abu‐Rmaileh Amro, Sara; Zarivach, Raz; Zangen, David; Lavi, Eran; Haim, Alon; Parvari, Ruti; Abu‐Libdeh, Abdulsalam
Abstract: Aldosterone synthase deficiency (ASD) is a rare potentially life‐threatening genetic disorder that usually presents during infancy due to pathogenic variants in the CYP11B2 gene. Knowledge about CYP11B2 variants in the Arab population is scarce. Here, we present and analyze five Palestinian patients and their different novel pathogenic variants. Data on clinical presentation, electrolytes, plasma renin activity, and steroid hormone levels of five patients diagnosed with ASD were summarized. Sequencing of the CYP11B2 gene exons was followed by evolutionary conservation analysis and structural modeling of the variants. All patients were from highly consanguineous Palestinian families. The patients presented at 1–4 months of age with recurrent vomiting, poor weight gain, hyponatremia, hyperkalemia, and low aldosterone levels. Genetic analysis of the CYP11B2 gene revealed three homozygous pathogenic variants: p.Ser344Profs*9, p.G452W in two patients from an extended family, and p.Q338stop. A previously described pathogenic variant was found in one patient: p.G288S. We described four different CYP11B2 gene pathogenic variants in a relatively small population. Our findings may contribute to the future early diagnosis and therapy for patients with ASD among Arab patients who present with failure to thrive and compatible electrolyte disturbances.